Exploring the utilization of targeted intervention services by transgender individuals in Uttarakhand, India: a qualitative study - Khapre, Meenakshi; Sahoo, Krushna; Saxena, Vartika; Sinha, Smita; Luthra, Gagandeep; Joshi, Anubhuti (Frontiers in Public Health, 2024)
PurposeTransgender (TG) women face violence, discrimination, and stigma, which affect their mental health and hinder their access to targeted intervention (TI) services. This lack of access may increase the risk of human immunodeficiency virus/sexually transmitted infections (HIV/STIs). However, the utilization of TI services among transgender women in Uttarakhand, as well as across the country, remains understudied. The purpose of this study is to explore the utilization of TI services by the transgender community in Uttarakhand.MethodsThis qualitative study focused on non-government organizations (NGOs) that implement TI projects in Haridwar and Roorkee, Uttarakhand, India. From September 2023 to January 2024, 5 focus group discussions (FGDs) involving 24 transgender women and 9 in-depth interviews (IDIs) involving NGO staff were conducted. Thematic analysis, guided by the Anderson and Newman healthcare utilization model, was employed.ResultsSeveral barriers to service utilization were identified, including ritual beliefs, low health literacy, stigma, social isolation, financial insecurity, privacy concerns, and inefficient service delivery. Challenges in the implementation of the STI program and neglect of transgender women in health facilities were also reported. However, enabling factors such as trusted providers, supportive laws, and initiatives by NGOs and government agencies were recognized. Nonetheless, there remains a significant need for information on gender-affirming services and addressing other prevalent health issues within the transgender female community.ConclusionThe study underscores the interplay of individual, social, and service-related factors affecting healthcare access among transgender women. Inclusive and high-quality healthcare services are necessary to address the complex sociocultural aspects influencing transgender women’s healthcare access and utilization.